Decabromodiphenyl ethane exposure damaged the asymmetric division of mouse oocytes by inhibiting the inactivation of cyclin‐dependent kinase 1. Issue 4 (16th March 2021) - Shi, Feifei; Feng, Xizeng
Abstract: Decabromodiphenyl ethane (DBDPE) is a new brominated flame retardant and is widely added to flammable materials to prevent fire. Because it has been continuously detected in a variety of organisms and humans, it is important to reveal the biological toxicity of DBDPE. However, the influence of DBDPE for female reproduction is unclear. In this study, we investigated whether and how DBDPE exposure affects oocyte development. Female mice as a model were orally exposed to DBDPE by 0, 0.05, 0.5, 5, 50 μg/kg bw/day for 30 days (0.05 μg/kg bw/day is close to the environmental exposure concentration). We found that exposure of mice to DBDPE did not affect the first polar body extrusion (PBE) of oocytes. Strikingly, however, asymmetric division of oocytes was markedly impaired in 5 and 50 μg/kg bw/day DBDPE exposed group, which resulted in oocytes with larger polar bodies (PBs). Then, we further explored and found that DBDPE exposure inhibited the spindle migration and membrane protrusion in oocytes during anaphase of meiosis I (anaphase I), thereby impairing asymmetric division. Additionally, we found that DBDPE exposure suppressed the inactivation of cyclin‐dependent kinase 1 (Cdk1), resulting in the decrease of cytoplasmic formin2 (FMN2)‐mediated F‐actin polymerization in oocytes at the onset of anaphase I. Simultaneously, DBDPE exposure damaged the structural integrity of the spindle and the perpendicular relationship between spindle and cortex. These together led to the failure of spindle migration and membrane protrusion required for oocytes asymmetric division. Finally, DBDPE exposure injured the development of blastocysts, leading to blastocyst apoptosis.